Thomas Lickona’s Comprehensive Character Education Model and Its Relevance to the Islamic Education Curriculum: A Study of SD Plus Rahmat in Kediri - Shahzadi Hina Sain; Khorida Ubaidatus Syarifah; Kuni Rofi’atunnisa’; Moh Izza Romadhon (International Journal of Religion and Social Community, 2026)
This article examines the implementation of Thomas Lickona’s comprehensive character education model and its relevance to the Islamic Education curriculum at SD Plus Rahmat Kediri. The research employs a qualitative approach through literature review and field data collection, comprising document analysis, in-depth interviews with the headteacher and teachers, and observation of learning activities and character programmes. The analysis was conducted thematically by grouping the findings into three main pillars, namely moral knowing, moral feeling, and moral action, and relating them to the principles of Islamic ethics. The research findings indicate that the school successfully implemented the Lickona model through religious habit formation, teacher role modelling, a structured school culture, and collaboration with parents, thereby developing pupils’ moral competencies cognitively, affectively, and behaviourally. The novelty of this study lies in the development of an integrative model that combines the Lickona framework with Islamic ethical values through a school-culture-based approach. This study offers a contextual and practical implementation model to strengthen character education grounded in religious values in primary schools.